Synergism of duplicated Gasdermin Eb in Carassius auratus gibelio unveiling a regulatory amplification loop for pyroptosis - Yihui Fan; Miaomiao Wu; Caijiao Dai; Yuting Zhu; Junfa Yuan; Lijuan Li (Fish & Shellfish Immunology, 2026)

Typhoons-induced destruction and rapid reconstruction of the summer coastal upwelling system on a typical upwelling developing area: A case study in the Taiwan Strait - Xiaofang Fan; Fangfang Shu; Binxin Zheng; Yunpeng Lin; Yuting Lin; Fusheng Luo; Yunhai Li (Continental Shelf Research, 2026)

Calcium-driven adaptive microbial succession and metabolic shift towards chemical-biological synergistic phosphorus removal in anaerobic-aerobic-anoxic-hydroxyapatite (AOA-HAP) system - Miao Zhang; Yinlin Qi; Yuting Chen; Dongbin Wang; Yajun Fan; Jun Wu; Junjie Ji (Bioresource Technology, 2026)

CTAB-assisted synthesis of HoY2Ox composite oxide catalyst with highly exposed specific (211) plane for cyclohexene epoxidation - Yingjie Wang; Fang Wang; Yuting Luo; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu (Journal of Environmental Chemical Engineering, 2026)

Regulation of LPS-induced neuroinflammation in BV-2 cells by mung bean-derived chlorophyll metal salts via the NF-κB/MAPK signaling pathway - Yuting Su; Xinkun Wang; Jingwen Fan; Yunmei Li; Jingyao Wu; Rathna Silviya Lodi; Zhixin Wang; Lizeng Peng (Food Research International, 2026)

Single-atom Cu in TCPP-hydrogen-bonded organic framework/PFC-1 hydrogen-bonded organic framework Z-scheme heterojunctions for photocatalytic hydrogen production - Na Song; Yuting Zhu; Fan He; Mengnan Zhang; Mingfu Ye; Shengjun Liu; Kui Zhang (Chemical Engineering Journal, 2026)

Mechanism of α-amylase hydrolysis in maize and potato starches: Insight into outer shells and inner blocklets - Yuting Fan; Mengting Ma; Xinyu Zhang; Shuang-Kui Du; Zhongquan Sui; Harold Corke (Food Chemistry, 2026)

Deciphering the distribution of starch granule-associated proteins within maize and potato starch granules by α-amylase hydrolysis - Mengting Ma; Yuting Fan; Xinyu Zhang; Shuang-Kui Du; Zhongquan Sui; Harold Corke (Carbohydrate Polymers, 2026)

Retraction notice to “Response of C:N:P stoichiometry to long-term drainage of peatlands: Evidence from plant, soil, and enzyme” [Sci. Total Environ. 919 (2024) 170688] - Shengzhong Wang; Yaoyao Du; Shasha Liu; Junxiao Pan; Fan Wu; Yingzhuo Wang; Yuting Wang; Hongkai Li; Yanmin Dong; Zucheng Wang; Ziping Liu; Guodong Wang; et al. (Science of The Total Environment, 2026)

Enhanced removal of polycyclic aromatic hydrocarbons (PAHs) by biochar-immobilized laccase: Stability, reusability, and mechanistic insights - Longmiao Yuan; Jiayan Li; Yuting Wang; Xiaofeng Ma; Na Liu; Yingqin Wu; Beihang Zhang; Qiaohui Fan (Journal of Environmental Chemical Engineering, 2026)

Phosphorus dynamics in lake sediments under combined ecological restoration: A spatial chronosequence study of dredging and water management in Baiyangdian Lake - Liang Yang; Yong Fan; Haiqing Xu; Siyuan Pei; Yuting Ning; Ma Du; Liangting Jiang; Siyuan Chen; Dong Guo; Yuansheng Pei (Journal of Environmental Management, 2026)

Tuning the Cu/Zn ratio in copper-zinc phosphate catalysts: Mechanistic insights into activity and stability of anisole acetylation - Yuting Luo; Yingjie Wang; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu; Fang Wang (Fuel, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Glacial buffering maintains recent runoff stability amid warming and wetting in Central Asia - Youping Chen; Feng Chen; Heli Zhang; Huaming Shang; Yuting Fan; Lu Li; Hongfan Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Performance analysis and control strategies of a gas-electric hybrid high-temperature hot water supply system for industrial applications - Yawen Zheng; Junming Fan; Peng Jiang; Qiaoyun Wen; Junqin Wu; Xu Guan; Yuting Liu; Jun Cao; Liang Qiao; Wei Liu; Wei Teng (International Journal of Refrigeration, 2026)

Hybrid membrane-coated tetrahedral framework nucleic acid nanoparticles for targeted delivery of temozolomide in glioblastoma chemotherapy - Jinlong Yang; Tongyu Wang; Yuting Yang; Lu Jiang; Ruilian Chen; Rangrang Fan; Wenjuan Ma; Jianguo Xu; Yunfeng Lin (Chemical Engineering Journal, 2026)

A Microbial Odyssey: Reshaping Probiotic Destinies through Advanced Delivery Technologies - Ao Zhang; Yuting Rong; Yueyue Gao; Guibo Fan; Ayang Zhao; Sihua Qi (Probiotics and Antimicrobial Proteins, 2026)

Effects of different thermal processing methods on the nutritional components of whole highland barley and its hypoglycemic and hypolipidemic effects: β-glucan and polyphenols - Fan Xie; Huajia Dai; Yuting Yan; Yi Zhang; Jun Zhang; Zhou Zhang; Lianzhong Ai (Food Chemistry, 2026)

Air-water interfacial and foaming properties of various mung bean protein fractions: Effects of pH and salt concentration - Xuanyu He; Yuting Fan; Jiang Yi (Food Hydrocolloids, 2026)

Impacts of persistent underground coal fires on radial growth of Picea schrenkiana on the northern slope of the Tianshan Mountains - Tongwen Zhang; Dong Guo; Jinghui Song; Shulong Yu; Shengxia Jiang; Kailong Guo; Tianhao Hou; Xiaoxia Gou; Ruxianguli· Abudoureheman; Huaming Shang; Yuting Fan (Dendrochronologia, 2026)

The climatic response of inter- and intra-annual tree ring stable carbon isotopes of larch trees in the Qinling Mountains, central China - Mingyang Sun; Chao Li; Rong Fan; Yuting Fan; Feiyu Chen; Yuanjie Wang; Huan Zhang; Ninglian Wang (Dendrochronologia, 2026)

Hydrological mechanisms and vegetation–soil moisture decoupling in restored alpine grasslands of the Qinghai-Tibet Plateau mining areas - Xiaowei Guo; Yongsheng Yang; Shuping Zhang; Mengke Si; Bo Fan; Yuting Lan; Bencuo Li; Qian Li; Huakun Zhou; Zhenhua Zhang (Journal of Environmental Management, 2026)

HFPO-TA induces cardiac developmental damage in zebrafish by disrupting mitochondrial dynamics through FABP3 - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao (Environmental Research, 2026)

Dual effects of 6PPD at environmentally relevant concentrations on freshwater algae: Multi-omics reveals a shift in survival strategies from lipid-mediated adaptation to carbon-energy reallocation - Yuting Liu; Qin Fan; Bin Wang; Qiang Gao; Yi Chen; Xu Jing; Han Qu; Delin Qi; Mingyue Pang; Wei Wang (Journal of Hazardous Materials, 2026)

Impact of mung bean albumin-to-globulin ratio on the protein foaming properties: Explanation about protein physicochemical, molecular and interfacial properties - Xuanyu He; Yangxuan Yang; Yuting Fan; Jiang Yi (Food Hydrocolloids, 2026)

A Comprehensive Study of AAV Tropism in the Marmoset Brain - Kailun Fang; Hailin Liu; Yuting Yao; Zhen Xu; Xinyu Liu; Canbin Feng; Yuanhua Liu; Tong Li; Guannan Geng; Ruoxi Wu; Junhui Xia; Fan Yang; et al. (Neuroscience Bulletin, 2026)

Thioether and ether derivatives of diphyllin: synthesis and inducing tumor ferroptosis activity - Jianhang Han; Yujie Ma; Siwei Ji; Fan Yang; Qinyao Lu; Yuting Zhang; Yu Zhao (Natural Product Research, 2026)

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

Novel insights into the interaction of thioarsenates with ferrous-bearing minerals under anoxic conditions: Evidence from XAS analysis - Danni Zhang; Ying Wang; Fan Xiao; Yumeng Wang; Yuting Jin; Guang Liu; Yongfeng Jia (Journal of Hazardous Materials, 2026)

Development of pea protein nanofibrils-derived hydrogel mediated with EGCG for curcumin vehiculation: Characteristics, stability, and antimicrobial activity - Yuting Fan; Hailing Zhang; Ling Kang; Jiang Yi (Food Chemistry, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

Sevoflurane exposure in juvenile causes persistent learning and memory impairment via inducing endoplasmic reticulum stress in caenorhabditis elegans and mice - Ayang Zhao; Hongjiang Jin; Xiaofei Ma; Guibo Fan; Yueyue Gao; Yuting Rong; Siqi Sun; Ao Zhang; Sihua Qi (NeuroToxicology, 2025)

Application of feruloyl esterase BpFae03105 and xylanase XynAS Co-enzymolysis to produce ferulic acid from wheat bran - Han Lichun; Zhong Xiufang; Fu Zhilei; Yan Jinlong; Xiao Lin; Zhu Yuting; Liu Xiaoyan; Rana Abdul Basit; Wang Jinpeng; Yin Dafeng; Fan Guangsen (Biocatalysis and Agricultural Biotechnology, 2025)

Grassland degradation indirectly impacts soil carbon and nitrogen by altering nematode communities in permafrost area - Kunhe Liu; Lile He; Bo Fan; Yuzhang Li; Yuting Lan; Mengke Si; Bencuo Li; Yongsheng Yang; Ten Tse; Tsering Choekyi; Xiaowei Guo; Yigang Hu; et al. (Applied Soil Ecology, 2025)

The fungicide jinggangmycin stimulates fecundity of Nilaparvata lugens Stål via ILP/Foxo signaling - Xudong Zhao; Yuting Ding; Zhirou Duan; Di Deng; Zhiyue Mao; Yan Zhu; Xiaoxi Fan; Guohui Yu; Linquan Ge (Pesticide Biochemistry and Physiology, 2025)

Hydroisomerization performance of nanosized high-silica ZSM-48 catalysts synthesized via stepwise crystallization method - Wei Zhang; Yuting Wang; Jiangnan Xiang; Haiying Lu; Wenrui Jin; Yan Wang; Bo Qin; Weijiong Dai; Binbin Fan; Jiajun Zheng; Ruifeng Li (Fuel, 2025)

Application and mechanisms of high-salinity water desalination for enhancing oil recovery in tight sandstone reservoir - Yuting He; Yuetian Liu; Bo Zhang; Pingtian Fan; Fan Li; Rukuan Chai; Liang Xue (Desalination, 2025)

Iron-doped and nitrogen-deficient tubular carbon nitride enables synergistic photocatalysis-self-Fenton degradation of tetracycline - Fan Fan; Jiajie Yu; Junjie Jiang; Hao Xiu; Yuting Wang; Yongpeng Cui; Yajun Wang (Journal of Environmental Chemical Engineering, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Waterlogging disrupts soil-microbe-metabolite interactions in the pepper rhizosphere, driving wilt disease emergence - Fan Yang; Yuting Hong; Xiaoke Chang; Xin Wang; Miaomiao Liu; Weiwei Chen; Baoming Tian; Gongyao Shi; Qiuju Yao (Applied Soil Ecology, 2025)

Chronic low-level exposure to Pb, Hg, and Cd mixture triggers brain premature aging in rat - Jie Xie; Lu Ouyang; Jiajun Li; Shuo Yang; Qi Li; Yue Li; Lingyu Yan; Yihong Fu; Qijun Li; Yuting Xia; Xinling Chen; Ziyang Fu; et al. (Toxicology, 2025)

A metagenomics-based approach to understanding the transmission of healthcare-associated antimicrobial resistance in Pakistan - Muhammad Umer Asghar; Yuting Zhai; Ting Liu; Peixin Fan; Noor Ul Ain; Arsalan Haseeb Zaidi; Muhammad Tariq; Raul C. Mainar-Jaime; Kwangcheol C. Jeong (Journal of Hazardous Materials, 2025)

Analysis of Morphological Characteristics of Male and Female Gymnocypris eckloni Herzenstein - Qiming Wang; Suxing Fu; Xiaoyi Chen; Yuting Duan; Luo Lei; Yawen Fan; Chaowei Zhou (Fishes, 2025)
Accurate sex identification is crucial for the artificial breeding of fish species, and identification based on phenotypic traits is the preferred method owing to its low cost and rapidity. This study aimed to investigate morphological differences between male and female Gymnocypris eckloni Herzenstein. A total of 166 G. eckloni individuals (83 males and 83 females) were included, and 20 morphological indicators, including head length, snout length, and body weight, were measured. Various analytical methods, such as correlation analysis, principal component analysis, discriminant analysis, and systematic cluster analysis, were used to compare the morphological characteristics of male and female G. eckloni. The result showed significant differences in morphological characteristics between male and female individuals (p ≤ 0.05). Principal component analysis revealed five main components that collectively contributed to 83.64% of the variance, primarily including body length, fork length, total length, and body weight, highlighting the significance of these components in sex differentiation. Subsequently, a mathematical model was constructed via discriminant analysis. This model demonstrated an accuracy of 79.5% and 73.5% in identifying male and female G. eckloni, respectively, with an overall accuracy of 76.50%. Furthermore, on analyzing the relationship between body length and body weight in G. eckloni, we found differences in growth patterns between sexes. In particular, female fish usually weighed more than male fish, which was consistent with the biological characteristics and energy distribution patterns of G. eckloni. These results suggest that sexual dimorphism in G. eckloni is primarily concentrated in body shape and head morphology, which provides a reliable basis for sex identification based on morphological differences.

Evolution of spatiotemporal variations in snow in the Tianshan Mountains and Pamir, Central Asia: An investigation by historical and projected dynamic downscaling simulations - Qian Li; Weili Duan; Tao Yang; Gulayozov Majid Shonazarovich; Yuting Fan; Chenxiang Ju; Aliyaer Aihaiti; Lanhai Li (Journal of Hydrology, 2025)

Formation, characterization and delivery of quercetin-loaded α-lactalbumin fibril-based hydrogels through metal ions - Ling Kang; Hailing Zhang; Yuting Fan; Jiang Yi (Food Bioscience, 2025)

Gut microbiota mediated immunoregulatory effects of Dendrobium officinale polysaccharides-selenium nanoparticles complexes - Yan Long; Jiajing Yang; Hongfei Ji; Yuting Fan; Keyao Dai; Wenjie Ding; Haiyu Ji; Juan Yu (Food Bioscience, 2025)

Enhanced stabilization and curcumin delivery by covalent NaCas-EGCG modified proso millet protein nanoparticles in Pickering emulsions - Yuting Fan; Jing Ren; Xinyi Li; Pingping Zhang; Yang Yao; Xiuzhu Yu; Shuang-kui Du (Food and Bioproducts Processing, 2025)

Characterization of PM2.5-borne heavy metal pollution from industrial sources and human health risk assessment - Xiaoteng Ji; Xinyi Ma; Hongya Niu; Yuting Tian; Hao Zhu; Runshuang Shi; Jinxi Wang; Jingsen Fan (Atmospheric Environment, 2025)

Effects of chemical modifications on allergenicity and functional properties of silkworm pupae proteins - Songyuan Huang; Xue Feng; Wenqi Yue; Philippe Madjirebaye; Xuchao Deng; Yuting Fan; Jiamin Chen; Xuli Wu (Food Chemistry, 2025)

Efficient capacitive deionization of N-doped g-C3N4 quantum dots modified carbon cloth electrode under alkaline conditions - Huating Jiang; Kaiyuan Li; Yuting Qiao; Weiyi Zeng; Hao Huang; Chao Zhang; Zhengyang Fan; Hui Hu (Desalination, 2025)

Fabrication, characteristics and properties of α-lactalbumin fibril-derived hydrogels: Effects of metal ions type - Ling Kang; Rizwan Ahmed Bhutto; Yuting Fan; Jiang Yi (Food Chemistry, 2025)

Recent trends in co-encapsulation of probiotics with prebiotics and their applications in the food industry - Rizwan Ahmed Bhutto; Noor ul ain Hira Bhutto; Hidayatullah Mahar; Santosh Khanal; Mingwei Wang; Shahid Iqbal; Yuting Fan; Jiang Yi (Trends in Food Science & Technology, 2025)

Design, synthesis and systemic acquired resistance of 2-benzothiadiazolylquinoline-4-carboxamides by COI1 based virtual screening - Xiaoyu Liu; Hongwei Yang; Yaru Sun; Yuting Huang; Shuang Hong; Haolin Yuan; Wei Gao; Liangfu Tang; Zhijin Fan (Molecular Diversity, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Greater moisture impacts on radial growth of Larix sibirica in the eastern Altay Mountains since the 1990s - Xiaoxia Gou; Tongwen Zhang; Shulong Yu; Huaming Shang; Ruibo Zhang; Li Qin; Kexiang Liu; Shengxia Jiang; Dong Guo; Yuting Fan; Ruxianguli Abudureheman; Heli Zhang (International Journal of Biometeorology, 2025)

Spatial expansion characteristics of rural settlements and its response to determinants in Hangzhou Bay Urban Agglomeration, China: Geospatial modeling using multiscale geographically weighted regression (MGWR) - Zijuan Zhao; Beilei Fan; Xinwei Du; Xueqi Liu; Shihao Xu; Yudong Cao; Yuting Wang; Qingbo Zhou (Journal of Cleaner Production, 2024)

Formation, physiochemical stability, and bioaccessibility of quercetin-loaded α-lactalbumin amyloid-like fibril nanocomposite with ultrasound and its application in yogurt - Ling Kang; Rizwan Ahmed Bhutto; Noor ul ain Hira Bhutto; Yuting Fan; Jiang Yi (Food Hydrocolloids, 2024)

Potato protein as an emerging high-quality: Source, extraction, purification, properties (functional, nutritional, physicochemical, and processing), applications, and challenges using potato protein - Rizwan Ahmed Bhutto; Noor ul ain Hira Bhutto; Santosh Khanal; Mingwei Wang; Shahid Iqbal; Yuting Fan; Jiang Yi (Food Hydrocolloids, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Experimental study on the effect of CO2 dynamic sequestration on sandstone pore structure and physical properties - Yuting He; Yuetian Liu; Jingpeng Li; Pingtian Fan; Xinju Liu; Rukuan Chai; Liang Xue (Fuel, 2024)

External surface Al-rich ZSM-48 zeolite with high efficient n-dodecane hydroisomerization activity - Wei Zhang; Jiangnan Xiang; Yuting Wang; Shuzhen Wang; Mengxi Ma; Yan Wang; Bo Qin; Weijiong Dai; Binbin Fan; Jiajun Zheng; Ruifeng Li (Fuel, 2024)

Formation of pea protein amyloid-like nanofibrils-derived hydrogels mediated by epigallocatechin gallate - Hailing Zhang; Ling Kang; Rizwan Ahmed Bhutto; Yuting Fan; Jiang Yi (Food Chemistry, 2024)

Simultaneously blocking ANGPTL3 and IL-1β for the treatment of atherosclerosis through lipid-lowering and anti-inflammation - Hanqi Wang; Xiaozhi Hu; Yuting Zhang; An Zhu; Jiajun Fan; Zhengyu Wu; Xuebin Wang; Wei Hu; Dianwen Ju (Inflammation Research, 2024)

Decoding the intestinal response to heat stress in Gymnocypris eckloni: Insights from a thorough analysis of microbiome and transcriptome - Chaowei Zhou; Yuting Duan; Junting Li; Suxing Fu; Shuhao Bai; Yutong Zhuang; Hejiao Li; Yinhua Zhou; Jian Shen; Rongpan Zhou; Fan Yang; Zhichao Liu; et al. (Aquaculture, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

Characteristics, physicochemical stability and in vitro release of curcumin-loaded glycated bovine serum albumin nanofibrils: Effects of molecular weight of saccharide - Yuting Fan; Chao Gan; Hailing Zhang; Jiang Yi (Food Hydrocolloids, 2024)

Polystyrene nanoplastics induce lipophagy via the AMPK/ULK1 pathway and block lipophagic flux leading to lipid accumulation in hepatocytes - Zhuying Fan; Yukang Zhang; Yuting Fang; Huiyuan Zhong; Tingting Wei; Huraira Akhtar; Jiahuai Zhang; Man Yang; Yanbo Li; Xianqing Zhou; Zhiwei Sun; Ji Wang (Journal of Hazardous Materials, 2024)

Interception of internal phosphorus release from sediments by lanthanum-modified shrimp shell biochar in two application modes - Fulong Cheng; Zuo Zhang; Changxin Zhao; Yuting Peng; Maoyu Liao; Jianxin Fan (Journal of Cleaner Production, 2024)

Centrifuge shaking table tests on tiered reinforced soil retaining walls subjected to the excitations of near-field ground motions - Cheng Fan; Xuejun Liu; Yuting Zhang; Xiaoyu An; Huabei Liu (Geotextiles and Geomembranes, 2024)

Assessing the relative contributions, combined effects and multiscale uncertainty of future land use and climate change on water-related ecosystem services in Southwest China using a novel integrated modelling framework - Xuenan Ma; Ping Zhang; Lianwei Yang; Yuting Qi; Jiexuan Liu; Lei Liu; Xin Fan; Kang Hou (Sustainable Cities and Society, 2024)

Pathogenic fungi synergistically cooperate with Serratia marcescens to increase cockroach mortality - Haizheng Zhao; Meng Jiang; Xuejun Wang; Huiyuan Gao; Yuting Zhang; Jingjing Wang; Xuexia Zhang; Dongqin Zhao; Fan Zhang (Pesticide Biochemistry and Physiology, 2024)

Polyelectrolyte nanocomplex from sodium caseinate and chitosan as potential vehicles for oil encapsulation by flash nanoprecipitation - Rizwan Ahmed Bhutto; Noor ul ain Hira bhutto; Shahid Iqbal; Salim Manoharadas; Jiang Yi; Yuting Fan (Food Hydrocolloids, 2024)

Studies into confined methane adsorption in shale nanopores using a simplified local density model - Xianwei Zeng; Bobo Li; Zheng Gao; Jianhua Li; Haosheng Song; Yunna Ding; Yuting Fan (Chemical Engineering Journal, 2024)

Bovine α-lactalbumin: Source, extraction, techno-functional properties, and applications as a (nano-) delivery system for nutraceuticals - Rizwan Ahmed Bhutto; Noor ul ain Hira Bhutto; Yuting Fan; Ling Kang; Mingwei Wang; Shahid Iqbal; Jiang Yi (Trends in Food Science & Technology, 2024)

Life cycle assessment for evaluation of novel solvents and technologies: A case study of flavonoids extraction from Ginkgo biloba leaves - Xuan Wang; Yuting Wei; Zhenyan Fan; Yueyuan Chen; Zhifang Cui (Science of The Total Environment, 2024)

RETRACTED: Response of C:N:P stoichiometry to long-term drainage of peatlands: Evidence from plant, soil, and enzyme - Shengzhong Wang; Yaoyao Du; Shasha Liu; Junxiao Pan; Fan Wu; Yingzhuo Wang; Yuting Wang; Hongkai Li; Yanmin Dong; Zucheng Wang; Ziping Liu; Guodong Wang; et al. (Science of The Total Environment, 2024)

Study of the influence of warehousing conditions on the aging durability of bamboo - Hao Jia; Yuting Yang; Wenhui Su; Shaohui Fan; Haoyu Chu (Journal of Cleaner Production, 2024)

Ultrasonic pretreatment and epigallocatechin gallate incorporation enhance the formation, apparent viscosity, and antioxidant activity of pea protein amyloid-like fibrils - Xiaoting Chen; Jiang Yi; Zhen Wen; Yuting Fan (Food Hydrocolloids, 2024)

Human CYP1A1-activated aneugenicity of aflatoxin B1 in mammalian cells and its combined effect with benzo(a)pyrene - Huanhuan Wang; Qin Fan; Qian Liang; Yao Wu; Zhongming Ye; Haipeng Wu; Qian Sun; Huanwen Tang; Yungang Liu; Qizhan Liu; Yuting Chen (Chemico-Biological Interactions, 2024)

An Understanding of the Relationship Between Mixing Performance and Power Consumption in a High-Shear Wet Granulation Pre-mixing - Zeng Liu; Chunling Liu; Renyu Fan; Yuting Wang; Linxiu Luo; Yanling Jiang; Jincao Tang; Zheng Lu; Libo Chen; Shuangkou Chen; Tianbing Guan; Chuanyun Dai (Journal of Pharmaceutical Innovation, 2024)

Long non-coding RNA ENSMUST00000197208 promotes a shift in the Th17/Treg ratio via the P2X7R-NLRP3 inflammasome axis in collagen-induced arthritis - Yuting Pan; Yan Wu; Yingying Liu; Panpan Wang; Hui Huang; Jing Jin; Yuying Fang; Shuoyin Huang; Zhidan Fan; Haiguo Yu (Immunologic Research, 2024)

Characteristics analysis of solid waste generation and carbon emission of beer production in China - Mengqi Fan; Tao Zhou; Ziye Zhao; Yuting Du; Siyan Liu; Zihan Bi; Jiaqi Lu; Hongping He; Lei Li; Xuya Peng; Xiaofeng Gao; Yilu Gu (Environmental Research, 2024)

Improving the functionality of pea protein with laccase-catalyzed crosslinking mediated by chlorogenic acid - Jiang Yi; Xiaoting Chen; Zhen Wen; Yuting Fan (Food Chemistry, 2024)

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

The fate of arsenic during the crystallization process of FeIII oxyhydroxides: Effect of reaction media, pH value, and Fe/As molar ratio under relatively low arsenic loading - Danni Zhang; Yuting Jin; Yumeng Wang; Shaofeng Wang; Fan Xiao; Ying Wang; Duo Wang; Dake Xu; Fuhui Wang; Yongfeng Jia (Science of The Total Environment, 2023)

Transcriptome analysis revealed that short-term stress in Blattella germanica to β-cypermethrin can reshape the phenotype of resistance adaptation - Huiyuan Gao; Yanan Zang; Yuting Zhang; Haizheng Zhao; Wenxiao Ma; Xingyu Chen; Jingjing Wang; Dongqin Zhao; Xuejun Wang; Yanhong Huang; Fan Zhang (Pesticide Biochemistry and Physiology, 2023)

DNA integrity under alkaline conditions: An investigation of factors affecting the comet assay - Erik Bivehed; Björn Hellman; Yuting Fan; Jakob Haglöf; Sonja Buratovic (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

G protein-coupled estrogen receptor activation by bisphenol-A disrupts lipid metabolism and induces ferroptosis in the liver - Wanqiu He; Zhangshan Gao; Shuhui Liu; Lei Tan; Yuting Wu; Jiwen Liu; Ziyi Zheng; Wentao Fan; Yan Luo; Zeguo Chen; Suquan Song (Environmental Pollution, 2023)

Electric vehicle routing problem considering energy differences of charging stations - Lijun Fan; Changshi Liu; Bo Dai; Junyu Li; Zhang Wu; Yuting Guo (Journal of Cleaner Production, 2023)

Preparation of bio-jet fuels by a controllable integration process: Coupling of biomass fermentation and olefin polymerization - Yuehui Luo; Rui Zhang; Yuting He; DanFeng Lou; Rui Zhu; Can Zhu; Minghui Fan; Quanxin Li (Bioresource Technology, 2023)

Correction to: Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Can the development of renewable energy in China compensate for the damage caused by environmental pollution to residents’ health? - Chenggang Li; Xiangbo Fan; Yuting Wang; Zuogong Wang; Yunxiao Dang; Yuanzheng Cui (Environmental Science and Pollution Research, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Industrial wastewater source tracing: The initiative of SERS spectral signature aided by a one-dimensional convolutional neural network - Yuting Huang; Bingxue Yuan; Xueqing Wang; Yongsheng Dai; Dongmei Wang; Zhengjun Gong; Junmin Chen; Li Shen; Meikun Fan; Zhilin Li (Water Research, 2023)

Status and prospects of tree-ring research in Central Asia - Tongwen Zhang; Kexiang Liu; Yuting Fan; Shulong Yu; Ruibo Zhang; Huaming Shang; Yujiang Yuan; Wenshou Wei; Qing He; Heli Zhang; Bakytbek Ermenbaev; Rysbek Satylkanov; et al. (Dendrochronologia, 2023)

Climate response of Picea schrenkiana based on tree-ring width and maximum density - Xiaoxia Gou; Tongwen Zhang; Shulong Yu; Kexiang Liu; Ruibo Zhang; Huaming Shang; Li Qin; Yuting Fan; Shengxia Jiang; Heli Zhang; Dong Guo (Dendrochronologia, 2023)

The free-standing N-CoO matrix towards optimizing dual-electrodes for high-performance Li-O2 batteries - Weiwei Wang; Hao Wan; Wenlong Cai; Yuting Fang; Zhechen Fan; Yongchun Zhu; Yitai Qian (Chemical Engineering Journal, 2023)

Cucumis sativus PHLOEM PROTEIN 2-A1 like gene positively regulates salt stress tolerance in cucumber seedlings - Yuyang Si; Huaifu Fan; Hongjie Lu; Yapeng Li; Yuting Guo; Chen Liu; Li’ang Chai; Changxia Du (Plant Molecular Biology, 2023)

Spatial and temporal characteristics of pollution loads in Tuojiang River watershed located in Sichuan Province, Southwest of China - Yuting Xiao; Min Fan; Jing Yao; Xiaoying Liang; Can Cai; Yuanzhe Wang; Weiguo Tu (Environment, Development and Sustainability, 2023)

Numerical Analysis of Flow Characteristics in Impeller-Guide Vane Hydraulic Coupling Zone of an Axial-Flow Pump as Turbine Device - Fan Yang; Zhongbin Li; Yuting Lv; Jindong Li; Guangxin Zhou; Ahmed Nasr (Journal of Marine Science and Engineering, 2023)
An axial-flow pump as a turbine (PAT), as compared to the conventional Francis turbine, has the advantages of not being restricted by the terrain and having lower cost to reverse the pump as a turbine for power generation. When an axial-flow pump is reversed as a turbine, the internal flow pattern is more complicated than when in the pump mode, which can cause instability in the whole system and result in degradation of the hydraulic performance and structural vibration. The impeller and guide vane are the core of the axial-flow PAT unit. This research compares the experimental and numerical simulation results in order to verify the energy performance and pressure pulsation signal of the axial-flow PAT. The unsteady flow regime, fluid force, and pressure pulsation characteristics of the impeller-guide vane hydraulic coupling zone are analyzed in detail. The findings demonstrate that both the dominant frequency of the fluid force pulsation signal and the flow field pressure pulsation signal appear at 3 times of the rotation frequency. The blade passing frequency (BPF) of the impeller is the dominant frequency, and other frequency components are also dominated by the harmonic frequency of the BPF. The impeller and guide vane are primarily subject to radial fluid force. Under partial working conditions, the pressure pulsation intensity in the flow field greatly increases, and the pressure pulsation amplitude at the guide vane outlet and impeller outlet appears to be more sensitive to the flow rate change.

One-pot synthesis of novel flower-like LaCO3OH adsorbents for efficient scavenging of phosphate from wastewater - Fulong Cheng; Fangui Nie; Yuting Fan; Dan Huang; Yinian Wang; Jianxin Fan (Environmental Science and Pollution Research, 2023)

New approaches to modeling the critical refreezing length of a Philberth melt probe for ice sheet exploration - Yazhou Li; Pavel G. Talalay; Xiaopeng Fan; Bing Li; Liang Xu; Yuting Ye; Yue Wang (Polar Science, 2023)

Spatial–temporal characteristics of corrected total phosphorus pollution loads from agricultural non-point sources in Tuojiang River watershed, Sichuan Province of southwestern China - Jing Yao; Min Fan; Yuting Xiao; Xiaoying Liang; Can Cai; Yuanzhe Wang (Environmental Science and Pollution Research, 2023)

Potential influence of fine aerosol chemistry on the optical properties in a semi-arid region - Pengfei Tian; Naiyue Zhang; Jiayun Li; Xiaolu Fan; Xu Guan; Yuting Lu; Jinsen Shi; Yi Chang; Lei Zhang (Environmental Research, 2023)

Selective removal of Hg(II) by UiO-66-NH2 modified by 4-quinolinecarboxaldehyde: from experiment to mechanism - Yuting Hu; Shixing Wang; Libo Zhang; Fan Yang (Environmental Science and Pollution Research, 2023)

Risk and benefit assessment of potential neurodevelopment effect resulting from consumption of cultured largemouth bass (Micropterus salmoides) in China - Yuting Yin; Xi Chen; Yuan Gui; Jianmin Zou; Qian Wang; Liping Qiu; Limin Fan; Shunlong Meng; Chao Song (Environmental Science and Pollution Research, 2022)

Numerical and Experimental Analysis of Transient Flow Field and Pressure Pulsations of an Axial-Flow Pump Considering the Pump–Pipeline Interaction - Fan Yang; Zhongbin Li; Jianguo Fu; Yuting Lv; Qingwei Ji; Hongfu Jian (Journal of Marine Science and Engineering, 2022)
The internal flow in a vertical axial-flow pump is a complex unsteady three-dimensional viscous flow. An unstable flow often produces complex flow phenomena such as flow separation, vortices, and secondary reflux, which reduces the operating efficiency of the pump and can endanger safety and stability. In this paper, computational fluid dynamics is used to calculate the flow characteristics in an axial-flow pump using the shear stress transport and curvature correction (SST-CC) model for turbulence modified to account for the rotational curvature. Furthermore, the dependability of the numerical results was confirmed by a test with an actual model of a pump. The transient deviation angle at the impeller inlet of the pump, the stream field attributes in various spanwise parts of the impeller and guide vane, and the velocity distributions at the impeller inlet and outlet were analyzed. The omega method was utilized to recognize the vortex structure inside the guide vane. Moreover, the development of the transient vortex structure inside the guide vane was studied. As the flow rate increased, the scale and turbulent kinetic energy of the vortex structure gradually decreased. The time-domain graph for the impeller inlet is clearly periodic, with three peaks and three troughs in an impeller rotational period. The dominant frequency in the spectrum at each monitoring point was basically the blade frequency, and the secondary dominant frequency was twice the blade frequency.

Microalgal-bacterial granular sludge process outperformed aerobic granular sludge process in municipal wastewater treatment with less carbon dioxide emissions - Dabin Guo; Xuechun Zhang; Yuting Shi; Baihui Cui; Jie Fan; Bin Ji; Julin Yuan (Environmental Science and Pollution Research, 2021)

Transcriptomic Analysis of Pacific Oyster (Crassostrea gigas) Zygotes Under Hypotonic Triploid Induction - Yangchun Li; Zhaoping Wang; Yuting Cui; Peizhen Ma; Xuekai Zhang; Chao Fan (Journal of Ocean University of China, 2021)

Inulin catabolism in Saccharomyces cerevisiae is affected by some key glycosylation sequons of invertase Suc2 - Fan Yang; Xinyu Zhang; Yuting Lu; Biying Wang; Xiaoyi Chen; Zhen Sun; Xianzhen Li (Biotechnology Letters, 2020)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Retraction Note to: The Clinical Utility of Matrix Metalloproteinase 9 in Evaluating Pathological Grade and Prognosis of Glioma Patients: A Meta-Analysis - Xiangshan Yang; Shunzeng Lv; Yuting Liu; Daotang Li; Ranran Shi; Zhenyu Tang; Jianzhen Fan; Zhongfa Xu (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: The Clinical Utility of Matrix Metalloproteinase 9 in Evaluating Pathological Grade and Prognosis of Glioma Patients: A Meta-Analysis - Xiangshan Yang; Shunzeng Lv; Yuting Liu; Daotang Li; Ranran Shi; Zhenyu Tang; Jianzhen Fan; Zhongfa Xu (Molecular Neurobiology, 2015)

Proteomic characterization of silicon-mediated resistance against Ralstonia solanacearum in tomato - Yuting Chen; Min Liu; Lei Wang; Weipeng Lin; Xueying Fan; Kunzheng Cai (Plant and Soil, 2015)

Cloning, characterization and functional analysis of the role MhNCED3, a gene encoding 9-cis-epoxycarotenoid dioxygenase in Malus hupehensis Rehd., plays in plant tolerance to osmotic and Cd2+ stresses - Weiwei Zhang; Hongqiang Yang; Shuzhen You; Yuting Xu; Kun Ran; Shulei Fan (Plant and Soil, 2014)

BRG1 variant rs1122608 on chromosome 19p13.2 confers protection against stroke and regulates expression of pre-mRNA-splicing factor SFRS3 - Xin Xiong; Chengqi Xu; Yuting Zhang; Xiuchun Li; Binbin Wang; Fan Wang; Qin Yang; Dan Wang; Xiaojing Wang; Sisi Li; Shanshan Chen; Yuanyuan Zhao; et al. (Human Genetics, 2014)

Changes in daily climate extremes in the arid area of northwestern China - Huaijun Wang; Yaning Chen; Shi Xun; Dongmei Lai; Yuting Fan; Zhi Li (Theoretical and Applied Climatology, 2013)

SP1 suppresses phorbol 12-myristate 13-acetate induced up-regulation of human regucalcin expression in liver cancer cells - Hong Xu; Peihua Ni; Changqiang Chen; Yuting Yao; Xiaoping Zhao; Guanxiang Qian; Xianqun Fan; Shengfang Ge (Molecular and Cellular Biochemistry, 2011)